Blended Learning in Integrated Science Learning by a WISE Approach in Homeschooling - Tryanto, Agus; Sukardjo, Moch; Siregar, Eveline (Universitas Pendidikan Ganesha, 2021)
The lack of variety of learning is carried out by Homeschooling, while Homeschooling is required to be more creative, independent, and innovative. Blended learning will be an innovative learning option and according to the character of Homeschooling. This study aims to develop blended learning in science subjects with the WISE approach in Homeschooling. The research is entitled development research (R&D). The development method uses a flipped learning model with a web-based design model with data collection using data triangulation. The instrument used to collect data is a questionnaire. The product will go through an evaluation process from experts and evaluate its feasibility and effectiveness. Expert reviews consist of reviews of media experts and learning design experts and reviews of material and language experts. The feasibility stage is carried out by one-to-one test, small group test, and field test. In comparison, the effectiveness test is carried out to summative evaluation by calculating the N-Gain score. The final result states that blended learning is feasible with an average of 3.5 on expert reviews, which is very good and effective with the calculation results of the average N-Gain 0.61 in the excellent category. So with Blended Learning, learning in Homeschooling becomes creative, innovative, and independent. The research implication is that the application of blended learning in Homeschooling will increase a pleasant learning atmosphere.